Necesidad de incluir un artículo en el código integral penal para establecer una sanción de tipo pecuniaria cuando se abandona por más de 90 días una denuncia presentada por violencia psicológica hacia la mujer y demás miembros del núcleo familiar - Espinoza Reyes, Juan Carlos (2017)
From the force of the Comprehensive Criminal Code went into effect the new crime of psychological and physical violence against women and members of the family, which the caseload both in the courts and prosecutors' offices in the country has increased noticeably. But this, not all complaints are properly informed, even becoming part of vengeance by one party, as it has been shown that this crime has been used for delayed claiming alimony, or by discussions product inheritances or to do harm to people. It has also raised complaints of minor fights that are oversized, as if coming to terms forget the complaint, not counting the cost to the Ecuadorian State and delay of justice to people who truly need it. This situation is likewise may show that Article 155 states as part of the family unit are considered members of the family or to the spouse, the common-law partner or a partner, partner, parents, children, sisters, brothers, relatives up to the second degree and persons with whom it is determined that processing or processed family maintains or has maintained, intimate, emotional, marital ties, interaction, dating or cohabitation situation for my standpoint It is not the right one because it could well denounce a roommate to another friend of domestic violence For all the above consider wise to include a sanction of a pecuniary nature to the person who does not go to the justice correctly denouncing this crime, and to abandon the cause for more than 90 days, because from my point of view would be enough time for the authority to determine that there is a lack of interest in continuing with the same